A study of collective entrepreneurship model as an alternative in empowering Micro, Small and Medium Enterprise (MSME) cooperatives - Ang Swat Lin Lindawati (Journal of Economics, Business, and Accountancy Ventura, 2014)
Entrepreneurship is essentially a knowledge problem. The cognitive  underpinnings of entrepreneurship are the heart of the problem. Entrepreneurs rely on different types of knowledge when identifying and developing profit opportunities through their entrepreneurship. This study is an attempt to answer the question on maintaining and empowering entrepreneurial capability by focusing on the understanding of collective entrepreneurship as the development of individual entrepreneurship (traditional entrepreneurship). This study is using concurrent triangulation approach as a research method. It is a strategy employing mixed approach between quantitative and qualitative applied side by side or with the same time (within a span of time). The representative sampling is using purposive sampling of MSMEs and MSME Cooperatives in Malang. Structural Equation Modeling (SEM) method is implemented as an analysismodel of quantitative approach that uses value to answer the research problems and to achieve the objectives of this research. The results show that the existence and the empowerment of MSMEs and Cooperatives are triggered by the aspects of psychology and the ability of the in-dividual that become the internal aspects and institutional structure factor (external aspect) has a positive association with the performance of MSMEs and  cooperatives.